Dysregulation of the actin scavenging system and inhibition of DNase activity following severe thermal injury. Issue 4 (10th September 2019) - Dinsdale, R J; Hazeldine, J; Al Tarrah, K; Hampson, P; Devi, A; Ermogenous, C; Bamford, A L; Bishop, J; Watts, S; Kirkman, E; Dalle Lucca, J J; Midwinter, M; et al.
Abstract: Background: Circulating cell-free DNA (cfDNA) is not found in healthy subjects, but is readily detected after thermal injury and may contribute to the risk of multiple organ failure. The hypothesis was that a postburn reduction in DNase protein/enzyme activity could contribute to the increase in cfDNA following thermal injury. Methods: Patients with severe burns covering at least 15 per cent of total body surface area were recruited to a prospective cohort study within 24 h of injury. Blood samples were collected from the day of injury for 12 months. Results: Analysis of blood samples from 64 patients revealed a significant reduction in DNase activity on days 1–28 after injury, compared with healthy controls. DNase protein levels were not affected, suggesting the presence of an enzyme inhibitor. Further analysis revealed that actin (an inhibitor of DNase) was present in serum samples from patients but not those from controls, and concentrations of the actin scavenging proteins gelsolin and vitamin D-binding protein were significantly reduced after burn injury. In a pilot study of ten military patients with polytrauma, administration of blood products resulted in an increase in DNase activity and gelsolin levels. Conclusion: The results of this study suggest a novel biological mechanism for the accumulation of cfDNA following thermal injury by which high levels of actin released by damaged tissue cause a reduction in DNase activity. Restoration of the actin scavenging system could therefore restore DNase activity, and reduce the risk of cfDNA-induced host tissue damage and thrombosis. Graphical Abstract: Circulating cell-free DNA (cfDNA) is not found in healthy subjects but is readily detected after thermal injury and may contribute to the risk of multiple organ failure. The authors hypothesized that a postburn reduction in DNase protein/enzyme activity could contribute to the increase in cfDNA after thermal injury. The results of this study suggest a novel biological mechanism for the accumulation of cfDNA following thermal injury whereby high levels of actin released by damaged tissue cause a reduction in DNase activity. Restoration of the actin scavenging system could therefore restore DNase activity, and reduce the risk of cfDNA-induced host tissue damage and thrombosis. NET, neutrophil extracellular trap. DNAse activity reduced following thermal injury, likely driven in part by raised circulating actin